Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Masyarakat Naik Kereta Api Di Stasiun Simpang Haru Padang - Oktiva Sari, Rista; Jolianis, Jolianis; Wahyuni, Sri (Pendidikan Ekonomi, 2014)
AbstracÂ a railway transportation services using an implementation of the marketing mix which plays an important role in influencing the public in decision distinguishes it from other ground transportation to the same destination. purpose of this research was to determine the effect of marketing mix which includes: product, price, place, promotion, people, process, and physical evidence of the communitys decision to take the train at the station simpang haru padang .types of research used in this study was a descriptive study associative with research sites at the train station which is located at the simpang haru padang. In this research model used 120 respondents, namely people who are in thesimpang haru padang that station will travel by rail transport. data collection techniques used in the form of questionnaires, observations and interviews. the accuracy of data in the test validity and reliability test, the collected data were analyzed by descriptive analysis, test the classical assumption of normality test and multikolonieritas test, and test multiple linear reggresi.based on the results of the study: 1) the product significantly influence the decisions people take the train, 2) the price significantly influence community decisions by train, 3) where no significant impact prices significantly influence the decisions people take the train, 4) promotion places no effect significant price significantly influence peoples decision to take the train, 5) significantly influence the decisions people take the train, 6) process no significant effect on peoples decision to take the train, 7) physical evidence does not significantly influence the decisions people take the train.